2021
DOI: 10.1101/2021.01.07.21249401
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Timeliness of provisional United States mortality data releases during the COVID-19 pandemic: delays associated with electronic death registration system and weekly mortality

Abstract: All-cause mortality counts allow public health authorities to identify populations experiencing excess deaths from pandemics, natural disasters, and other emergencies. Further, delays in mortality reporting may contribute to misinformation because death counts take weeks to become accurate. We estimate the timeliness of all-cause mortality releases during the Covid-19 pandemic, and identify potential reasons for reporting delays, using 35 weeks of provisional mortality counts between April 3 and December 4, 20… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…While many deaths are processed nearly immediately, delays in reporting may lead to underestimates at a given timepoint [24] . Studies during the pandemic suggest that after five weeks, most states have reported 99% of their eventual NVSS-reported all-cause mortality for that time period, and after three weeks all but three states were over 80% complete, and most were over 90% complete [ 25 , 26 ]. While time delays mean our estimates are likely an undercount of mortality, it suggests that for the purposes of monthly time-trend analysis, the provisional mortality data is nearly complete, and monthly outcomes primarily reflect deaths within that month.…”
Section: Methods and Datamentioning
confidence: 99%
“…While many deaths are processed nearly immediately, delays in reporting may lead to underestimates at a given timepoint [24] . Studies during the pandemic suggest that after five weeks, most states have reported 99% of their eventual NVSS-reported all-cause mortality for that time period, and after three weeks all but three states were over 80% complete, and most were over 90% complete [ 25 , 26 ]. While time delays mean our estimates are likely an undercount of mortality, it suggests that for the purposes of monthly time-trend analysis, the provisional mortality data is nearly complete, and monthly outcomes primarily reflect deaths within that month.…”
Section: Methods and Datamentioning
confidence: 99%
“…In all cases, varying delays of notifications and lack of spatial granularity represent significant issues for data quality that may hamper the evaluation of interventions. For instance, it has been estimated that the delay in death reporting in the US ranges from 2 to 12 weeks depending on the state (Rosenbaum et al, 2021). Similarly, the CDC estimates that only 63% of deaths are reported within 10 days, with large variability across states.…”
Section: Discussionmentioning
confidence: 99%
“…Capturing information in a timely manner Delays in capturing cause-specific mortality information are a recurring theme in the literature. 28 In non-emergency settings, all information is filled by corresponding agencies/individuals such as the funeral director, the attending physician, and medical examiners in cases of non-natural deaths, and should be available through the national Civil Registration and Vital Statistics (CRVS) system in a timely manner. 29 Although the "report" of a death is rapidly available, details on the death certificate, including codes for the CoD can take weeks to process.…”
Section: Assessing Disaster or Crisis-related Mortality And Its Impac...mentioning
confidence: 99%